Postoperative pain after cesarean section: assessment and management in a tertiary hospital in a low-income country - Kintu, Andrew; Lubikire, Aggrey; Nabukenya, Mary T.; Igaga, Elizabeth; Bulamba, Fred; Semakula, Daniel; Olufolabi, Adeyemi J. (BMC health services research, 2019)
There is little information about the current management of pain after obstetric surgery at Mulago hospital in Uganda, one of the largest hospitals in Africa with approximately 32,000 deliveries per year. The primary goal of this study was to assess the severity of post cesarean section pain. Secondary objectives were to identify analgesic medications used to control post cesarean section pain and resultant patient satisfaction. We prospectively followed 333 women who underwent cesarean section under spinal anesthesia. Subjective assessment of the participants’ pain was done using the Visual Analogue Scale (0 to 100) at 0, 6 and 24 h after surgery. Satisfaction with pain control was ascertained at 24 h after surgery using a 2-point scale (yes/no). Participants’ charts were reviewed for records of analgesics administered. Pain control medications used in the first 24 h following cesarean section at this hospital included diclofenac only, pethidine only, tramadol only and multiple pain medications. There were mothers who did not receive any analgesic medication. The highest pain scores were reported at 6 h (median: 37; (IQR:37.5). 68% of participants reported they were satisfied with their pain control. Adequate management of post-cesarean section pain remains a challenge at Mulago hospital. Greater inter-professional collaboration, self-administered analgesia, scheduled prescription orders and increasing availability of analgesic drugs may contribute to improved treatment of postoperative pain with better pain scores.